A compensation endband: a structural endband for a book with uneven edges. Issue 2 (2nd July 2016) - Green, Arthur
Abstract: This paper describes a structural endband that was developed for use on MS. Laud Misc. 99 ; a late-medieval parchment manuscript recently rebound at the University of Oxford's Bodleian Library. Whilst the endbands were an important part of the new wooden board binding, it was challenging to work them on the tail edge of the book because of the uneven quires and the desire to use boards of equal height. The solution was to develop compensation which would support a straight endband that laced evenly onto both boards whilst maintaining its structural function.